Managerial control or feedback provision: How perceptions of algorithmic HR systems shape employee motivation, behavior, and well‐being - Edwards, Martin R.; Zubielevitch, Elena; Okimoto, Tyler; Parker, Stacey; Anseel, Frederik (Human Resource Management, 2024)
AbstractAlgorithmic HR systems are becoming a more prevalent interface between organizations and employees. Yet little research has examined how automated HR processes impact employee motivation. In a three‐wave study (NTime1 = 401; NTime2 = 379; NTime3 = 303), we investigated the motivational effects of HR systems that automatically capture—and make decisions based on—employee performance, and whether these effects depend on employee attributions regarding the organization's intended use of its automated HR metric system. Additionally, we test whether these motivational states affect employee task prioritization and emotional exhaustion. Results show that employees whose organizations use algorithmic HR systems, and who also attribute managerial control as intent to that system, experience higher levels of extrinsic motivation at work. This, in turn, predicts greater prioritization of metricized tasks and de‐prioritization of non‐metricized tasks. Conversely, employees who believe the purpose of algorithmic HR systems is to provide them with constructive feedback are more likely to experience intrinsic motivation, leading to reduced feelings of emotional exhaustion, greater prioritization of metricized tasks, but reduced non‐metricized behavior de‐prioritization. These results illustrate the critical importance of employee sensemaking around algorithmic HR systems as a precursor to the impact of such systems on employee motivation, behavior, and well‐being.